Adsorption of various compounds onto nanooxides unmodified and differently pretreated - V. M. Gun'ko; O. K. Matkovsky (Хімія, фізика та технологія поверхні, 2023)
Features of interfacial adsorbate/adsorbent phenomena depend on several factors: particulate morphology, texture, and structure of adsorbents, molecular weight, shape, and polarity of adsorbates; as well as prehistory of adsorbents pretreated under different conditions. All these factors could affect the efficiency of practical applications of not only adsorbents but also polymer fillers, carriers, catalysts, etc. Interactions of nonpolar nitrogen, hexane, benzene, weakly polar acetonitrile, and polar diethylamine, triethylamine, and water with individual (silica, alumina), binary (silica/alumina (SA)) and ternary (alumina/silica/titania, AST) nanooxides were studied using experimental and theoretical methods to elucidate the influence of the morphological and textural characteristics and surface composition of the materials on the adsorption phenomena. The specific surface area SX / ratio (X is an adsorbate) changes from 0.7 for hexane adsorbed onto amorphous silica/alumina SA8 with 8 wt. % Al2O3 (degassed at 200 °C) to 1.9 for acetonitrile adsorbed onto pure fumed alumina (treated at 900 °C). These changes are relatively large because of variations in orientation, lateral interactions, and adsorption compressing of organic molecules interacting with surfaces characterized by certain set and amounts of various active sites, as well as due to changes in the accessibility of pore surface for probe molecules of different sizes. Larger SX / > 1 values are observed for complex fumed oxides with larger primary nanoparticles, greater surface roughness, hydrophilicity, and Br?nsted and Lewis acidity of a surface. Both polar and nonpolar adsorbates can change the morphology and texture of aggregates of oxide nanoparticles, e.g., swelling of structures, compacted during various pretreatments, upon the adsorption of liquids. The studied effects should be considered upon practical applications of adsorbents, especially “soft” fumed oxides.